Things no one taught us about love - Vex King (London Bluebird Books, 2024)
THE SUNDAY TIMES BESTSELLER Things No One Taught Us About Love distils the ideas found in Vex King's Closer to Love, re-edited and presented in the warm, relatable style of his No. 1 bestseller Good Vibes, Good Life. This extraordinary book is for anyone looking to harness the power of the universe, and their own self-understanding, to manifest stronger, deeper relationships. Bestselling author of Good Vibes, Good Life, Vex King is back with a life-changing guide to strengthening your relationships by learning to love yourself, and understanding the true nature of love. Many of us expect romantic love to solve our problems and validate our worth. This burden strains modern relationships. Partners become frustrated when unable to meet each other$1 (Bs idealized and impossible demands. Broken dreams of a life-long romance can leave people feeling incomplete and hopping from one partner to another.It$1 (Bs no wonder we struggle, given that society fails to teach us about the true nature of love. We$1 (Bve been misled into thinking love is external - somewhere out there - rather than a force within us. Vex King dismantles the myths and misconceptions surrounding love and relationships. Packed with personal stories, expert advice and inspirational messages, Things No-one Taught Us About Love will help you understand how you love, create healthy habits, set boundaries that work for you, and heal unprocessed emotion and trauma.'A long-term relationship will die and be reborn a thousand times. It doesn$1 (Bt matter how long you are with someone, but how willing you are to stay open to the new versions of them (and yourself) that are certain to arise.' - Vex King 'A must read if you are seeking to elevate your relationships and your life.' - Yung Pueblo, New York Times #1 Bestselling author of Clarity & Connection and Lighter.s
Keywords: Applied Psychology